Construcciones sostenibles y certificaciones LEED en Colombia (2017)
In the monograph the concepts of sustainable construction and LEED certifications applied in Colombia will be analyzed. The consultation of documentary sources identify the differences between the two definitions, the characteristics that the constructions subject to certification must meet, the benefits, advantages and disadvantages. In addition, the certified constructions in the country are identified, the legal framework that favors sustainable construction in Colombia and the laws in the country with respect to international experiences considered successful in their application.